Crop price indemnified loans for farmers: A pilot experiment in rural Ghana - Karlan, Dean; Kutsoati, Ed; McMillan, Margaret S.; Udry, Christopher R. (International Food Policy Research Institute, 2010)
Farmers face a particular set of risks that complicate the decision to borrow. We use a randomized experiment to investigate (1) the role of crop-price risk in reducing demand for credit among famers and (2) how risk mitigation changes farmers' investment decisions. In rural Ghana, we offer farmers loans with an indemnity component that forgives 50 percent of the loan if crop prices drop below a threshold price. A control group is offered a standard loan product at the same interest rate. We find similar rates of loan uptake among all farmers and little significant impact of the indemnity component on uptake or other outcomes of interest, with the exception of higher likelihoods of garden egg cultivation and sales to market traders rather than at farmgate among recipients of indemnified loans.